2018
DOI: 10.1136/bmjopen-2018-022051
|View full text |Cite|
|
Sign up to set email alerts
|

Real-world effectiveness evaluation of budesonide/formoterol Spiromax for the management of asthma and chronic obstructive pulmonary disease in the UK

Abstract: ObjectivesBudesonide/formoterol (BF) Spiromax® is an inhaled corticosteroid/long-acting β2-agonist fixed-dose combination (FDC) inhaler, designed to minimise common inhaler errors and provide reliable and consistent dose delivery in asthma and chronic obstructive pulmonary disease (COPD). We evaluated non-inferiority of BF Spiromax after changing from another FDC inhaler, compared with continuing the original inhaler.MethodsPatients with asthma and/or COPD who switched to BF Spiromax were matched (1:3) with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Exacerbations were documented in just over 1% (14/1230) of the participants. Despite an annualized rate could not be objectively calculated due to the 6 months follow-up, the projected rate of exacerbations of any severity is in alignment with the range noted from other interventional and observational studies 22,[30][31][32][33] . Contrary to the findings of certain randomized trials with high-dose ICS, metanalyses of interventional and observational studies concluded that fewer exacerbations occur with a fixeddose combination of ICS/LABA than with an ICS alone 34,35 .…”
Section: Discussionsupporting
confidence: 76%
“…Exacerbations were documented in just over 1% (14/1230) of the participants. Despite an annualized rate could not be objectively calculated due to the 6 months follow-up, the projected rate of exacerbations of any severity is in alignment with the range noted from other interventional and observational studies 22,[30][31][32][33] . Contrary to the findings of certain randomized trials with high-dose ICS, metanalyses of interventional and observational studies concluded that fewer exacerbations occur with a fixeddose combination of ICS/LABA than with an ICS alone 34,35 .…”
Section: Discussionsupporting
confidence: 76%
“…The authors concluded that the use of BF Spiromax ® in routine clinical practice by patients with asthma and COPD was not inferior to BF Turbuhaler ® in terms of disease control. Asthma patients who switched to BF Spiromax ® showed reduced exacerbations, lower SABA use, and greater treatment stability compared with those who continued BF Turbuhaler ® [45,46].…”
Section: Real-life Experience: Observational Studies With Spiromax® T...mentioning
confidence: 91%